New insights into the structural characteristics of irradiated crotamine - Oliveira, Karina Corleto; Spencer, Patrick Jack; Ferreira, Rui Seabra [UNESP]; Nascimento, Nanci (Biomed Central Ltd, 2015)
Background: Since ionizing radiation has the potential to alter the molecular structure and affect the biological properties of biomolecules, it has been successfully employed to attenuate animal toxins. The present study aimed to characterize the structural modifications on irradiated crotamine, a toxin from Crotalus durissus terrificus venom, using circular dichroism (CD), fluorescence, Fourier transformed infrared spectroscopy (FTIR), atomic force microscopy (AFM) and differential scanning calorimetry (DSC).Methods: A combination of size exclusion and ion-exchange chromatography was used to purify the peptide using crude venom. The pure toxin was then submitted to 2 kGy gamma irradiation doses from a cobalt-60 source. Native and irradiated crotamine were analyzed using a fluorescence spectrophotometer. Wavelength was fixed at 295 nm and fluorescence emission scans were collected from 300 to 400 nm. CD and FTIR techniques were used to identify the secondary structure of both samples. DSC analyses were performed at a starting temperature of 20 degrees C up to a final temperature of 90 degrees C. AFM provided a 3D profile of the surfaces of both crotamine forms adsorbed on mica.Results: Fluorescence spectroscopy showed that the quantum yield of the irradiated form decreased. CD spectra of native and irradiated crotamine solutions showed differences between the samples in wavelength, indicating that irradiation induced a transition of a small portion of the random coil regions towards an alpha-helical conformation. FTIR and CD showed that the native and irradiated crotamine spectra were different with regard to secondary structure. The thermodynamic analysis showed that irradiation caused changes in the calorimetric profile and CD showed that temperature-induced changes also occur in the secondary structure. Finally, AFM showed the possible formation of insoluble aggregates.Conclusions: Our results indicate that irradiation leads to progressive changes in the structure of the toxin, which could explain a decrease in myotoxic activity.
Keywords: Gamma radiation; Structural modifications; Crotamine; Snake venom; Crotalus durissus terrificus